2014
DOI: 10.1021/jp412662x
|View full text |Cite
|
Sign up to set email alerts
|

Dewetting Dynamics of a Solid Microsphere by Emulsion Drops

Abstract: A novel micropipet technique was developed to quantify the dewetting dynamics of individual microsphere particles by emulsified viscous crude oil drops in aqueous media. This technique allowed dynamic microscale receding contact angles of water to be measured in situ for solid−oil−water systems. System parameters, including modification of glass microspheres and characteristics of oil drops, were varied to study their effect on dewetting dynamics of the systems. Increasing solvent dosage in viscous oil was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…These studies demonstrated that bitumen could be competently recovered from oil/tar sands at a lower temperature with the assistance of a process aid. Recently, the working mechanisms of enhancing bitumen liberation -another essential step of bitumen extraction from oil sands via the addition of process aids including toluene, naphtha have been derived to guide design and selection of process aids Lin et al, 2014). To our best knowledge, there exists little information in open literature on the role of adding process aids in bitumen-air bubble interaction and attachment in water.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…These studies demonstrated that bitumen could be competently recovered from oil/tar sands at a lower temperature with the assistance of a process aid. Recently, the working mechanisms of enhancing bitumen liberation -another essential step of bitumen extraction from oil sands via the addition of process aids including toluene, naphtha have been derived to guide design and selection of process aids Lin et al, 2014). To our best knowledge, there exists little information in open literature on the role of adding process aids in bitumen-air bubble interaction and attachment in water.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…the angle between the two tangent lines at the three phase contact (TPC) point) were obtained by applying the automated angle acquisition method to analyzing still images, from which the dynamic and equilibrium contact angles were obtained. An example of this analysis on a real image is shown in Figure …”
Section: Methodsmentioning
confidence: 99%
“…A typical image analysis of contact angle determination using an in‐house developed shape fitting method …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations